In vitro GYNOGENESIS OF Jatropha curcas L. var ALJC01 - Guadalupe Lopez-Puc; Gilbert José Herrera-Cool; Alberto UC-Várguez; Ana Ramos-Díaz; Carlos Cecilio Góngora-Canul; Erick Alberto Aguilera-Cauich; Gregorio Martínez-Sebastián (Tropical and Subtropical Agroecosystems, 2021)
Background. Jatropha curcas L. is a crop whose oil can be converted to biodiesel. However, there is lack of varieties with high yields that limiting commercial production of the crop. An alternative is to obtain in vitro plants from unpollinated female gametophytes is known as gynogenesis which can provide an alternative to produce varieties with increased seed production. Objective. The objective was to establish a protocol for obtaining in vitro plants from unfertilized ovules of Jatropha curcas L. ovules. Methodology. The ovules were extracted from unfertilized inflorescences pretreated for 0, 1, 3 and 7 days at 2 to 5 ° C. Three combinations of plant growth regulator treatments were applied to culture media for induction of gynogenic calli. Gynogenic calli were cultured on MS basal medium with BAP and IBA for development of green, friable. The gynogenic calli from the development treatment were transferred to experiments to determine a regeneration treatment. The gynogenic plantlets were transferred to different treatments for root development. Results. The results show that pretreatment of inflorescences at 2 to 5°C had no significant effect on the number of ovules that formed friable white calli. Induction of gynogenic friable white calli occurred in the dark conditions, on half-strength Murashige and Skoog basal medium (½ MS) supplemented with two combinations of growth regulators: (i) 5.37 µM naphthalene acetic acid (NAA) combined with 6.65 µM 6-benzylaminopurine (BAP) and, (ii)8.05 µM NAA with 22.09 µM BAP. Development of green, friable, gynogenic calli under light–dark conditions was possible under treatment with complete Murashige and Skoog (1962) (MS) basal medium with 6.66 µM BAP and 4.9 µM indole-butyric acid (IBA).Friable green callus formed gynogenic embryos on MS basal medium supplemented with 22.09 µMBAP and 3.40 µM paclobutrazol (PBZ), embryos regeneration occurred in photoperiod conditions. Embryos were able to develop and convert to plantlets in the treatment on MS basal medium containing 2.22 µM BAP and 0.28 µM of indole-3-acetic acid (IAA). Root development of plantlets occurred in ½ MS basal medium with 18.65 µM IBA. Implications. A protocol of in vitro gynogenesis in Jatropha curcas would contribute to the improvement of its cultivation, reducing the time required for the generation of pure lines that would allow us to obtain varieties with increased seed production. Conclusions. The work presented here describes a reproducible protocol to produce plants in vitro from unfertilized ovules of Jatropha curcas L. This methodology will facilitate to obtain homozygotic lines with significant reduction in the time required by conventional methods.